2018
DOI: 10.1002/cncr.31229
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic differences in thyroid cancer incidence in the United States, 2007‐2014

Abstract: The diagnosis of small tumors is occurring at greater rates in whites (vs non-whites) and insured (vs Medicaid and uninsured) patients; consequently, these groups may be vulnerable to unnecessary tests and treatments or potentially aided by early detection. Guidelines that define postdetection interventions may be needed to limit the overtreatment of indolent and small papillary carcinomas. Cancer 2018;124:1483-91. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 33 publications
9
56
0
Order By: Relevance
“…Although our study focused on second rather than primary or index thyroid cancer, our finding about the association between gender and development of thyroid cancer is consistent with what is well known in the cancer epidemiology literature in the United States and globally about gender disparities in incidence of thyroid cancer . The significantly increased rate of SPTC in the Asian and Alaskan Native populations is consistent with recent incidence data that suggest there is also increasing incidence of both thyroid and HNC in both populations . This is important, because minority populations, including Asians and Alaskan Natives, may have poorer access to care and are less likely to present with early‐stage disease .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although our study focused on second rather than primary or index thyroid cancer, our finding about the association between gender and development of thyroid cancer is consistent with what is well known in the cancer epidemiology literature in the United States and globally about gender disparities in incidence of thyroid cancer . The significantly increased rate of SPTC in the Asian and Alaskan Native populations is consistent with recent incidence data that suggest there is also increasing incidence of both thyroid and HNC in both populations . This is important, because minority populations, including Asians and Alaskan Natives, may have poorer access to care and are less likely to present with early‐stage disease .…”
Section: Discussionsupporting
confidence: 89%
“…[37][38][39][40] The significantly increased rate of SPTC in the Asian and Alaskan Native populations is consistent with recent incidence data that suggest there is also increasing incidence of both thyroid and HNC in both populations. 39,[41][42][43] This is important, because minority populations, including Asians and Alaskan Natives, may have poorer access to care and are less likely to present with early-stage disease. 43 Because SPTC has a sixfold increased risk of death compared with primary thyroid cancer, it is especially important that these patients who develop SPTC and are racial minorities be supported to optimize their survival.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although race and ethnicity has an important role to play in the outlook of thyroid cancers [73][74][75], our study was not primarily aimed at studying these influences. However, all our patients were of African black population and of Nigerian descent.…”
Section: Discussionmentioning
confidence: 99%
“…Keane et al, in a review of eight retrospective cohort studies, with a total of 611 777 patients, found out that black and white patients have a higher proportion of follicular cancer, than Hispanics, though the later have a younger age at diagnosis [74]. Also, Week et al, reported that the white population has a greater proportion of diagnosed small tumors (papillary microcarcinomas) than non whites, attributable to their being more medical insured, and thereby susceptible to "unnecessary" investigations and overtreatment [75].…”
Section: Discussionmentioning
confidence: 99%
“…Recent genome‐wide association studies have identified the Chinese population to be at an increased risk for PTC. A recent study by Weeks et al found Asians to have a 40% higher odds than Caucasians of being diagnosed with PTC. Further, this study found Asians to have significantly higher age‐adjusted incidence rates for more advanced stage tumors when compared to Caucasians …”
Section: Introductionmentioning
confidence: 96%